Waste and the City The Crisis of Sanitation and the Right to Citylife - Mcfarlane, Colin (2023)
In an age of pandemics the relationship between the health of the city and good sanitation has never been more important. Waste and the City is a call to action on one of modern urban life 39 most neglected issues: sanitation infrastructure. The Covid-19 pandemic has laid bare the devastating consequences of unequal access to sanitation in cities across the globe. At this critical moment in global public health, Colin McFarlane makes the urgent case for Sanitation for All. The book outlines the worldwide sanitation crisis and offers a vision for a renewed, equitable investment in sanitation that democratises and socialises the modern city. Adopting Henri Lefebvre 39 concept of the right to the city 39, it uses the notion of 39 citylife 39 to reframe the discourse on sanitation from a narrowly-defined policy discussion to a question of democratic right to public life and health. In doing so, the book shows that sanitation is an urbanizing force whose importance extends beyond hygiene to the very foundation of urban social life.